2019
DOI: 10.1097/shk.0000000000001505
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide Hydroxamic Acid Alleviates Acute Lung Injury Induced by Severe Hemorrhagic Shock and Resuscitation in Rats

Abstract: Background: This study aimed to assess the severity of acute lung injury after mild or severe hemorrhagic shock and resuscitation, and to examine the therapeutic effects of suberoylanilide hydroxamic acid (SAHA) on lung injury. Methods: Mild and severe hemorrhagic shock were induced by total blood volume loss of 20% or 40%, respectively, which was maintained for 60 min. Then, resuscitation was performed by autologous blood and SAHA or a vehicle solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, this study showed that the HDAC inhibitor SAHA alleviated axonal injury and cognitive impairment in rats with SAH by elevating TDP-43 degradation by enhancing the acetylation of HSP70 by inhibiting HDAC1 enzymatic activity. SAHA is a well-recognized HDAC inhibitor that has also been confirmed to alleviate intracerebral hemorrhage 9 In addition, a recent study revealed that SAHA attenuated hemorrhagic shock and resuscitation-induced lung injury by repressing histone acetylation 37 . Hence, these findings support the role of SAHA in ameliorating SAH development by regulating the HDAC1/HSP70/TDP-43 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study showed that the HDAC inhibitor SAHA alleviated axonal injury and cognitive impairment in rats with SAH by elevating TDP-43 degradation by enhancing the acetylation of HSP70 by inhibiting HDAC1 enzymatic activity. SAHA is a well-recognized HDAC inhibitor that has also been confirmed to alleviate intracerebral hemorrhage 9 In addition, a recent study revealed that SAHA attenuated hemorrhagic shock and resuscitation-induced lung injury by repressing histone acetylation 37 . Hence, these findings support the role of SAHA in ameliorating SAH development by regulating the HDAC1/HSP70/TDP-43 axis.…”
Section: Discussionmentioning
confidence: 99%